2021
DOI: 10.3390/educsci11040150
|View full text |Cite
|
Sign up to set email alerts
|

Student Preferences Impact Outcome of Flipped Classroom in Dental Education: Students Favoring Flipped Classroom Benefited More

Abstract: Many reports in dental education showed that student learning improved with the flipped classroom method. However, there are few reports that describe how different subsets of students may benefit from the flipped classroom. In this study, we investigated how students’ preference for the flipped classroom impacted their learning outcome. We used a flipped classroom module on the physiology of the autonomic nervous system taught to year one Doctor of Dental Surgery students to test the hypothesis that students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
1
14
0
3
Order By: Relevance
“…Moreover, questions, answers, and results were at no point shared with students, thus preventing any bias. Similarly, this concept was also used in another study [ 14 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, questions, answers, and results were at no point shared with students, thus preventing any bias. Similarly, this concept was also used in another study [ 14 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies on flipped classrooms in the field of pediatric dentistry showed that students were satisfied with this method [ 12 , 13 ], providing the notable advantages of availability and access to online content and course materials, clickers to test knowledge in preparation for an exam, and in-class group discussions with the help of students questionnaires [ 12 ]. The results of a study with a flipped classroom on the physiology of the autonomic nervous system indicated that students spent more time learning, understood the content better, performed better in assessments, and preferred this method to a traditional lecture [ 14 ]. Another study on online lectures in dermatology showed that these were highly welcomed by students and may be a good means to improve the education of students in dermatology.…”
Section: Introductionmentioning
confidence: 99%
“…As an active methodology, the flipped classroom is defined by a series of characteristics that are linked to this type of pedagogical strategy, where the student is the protagonist of his or her learning process [23]. Thus, different studies have highlighted the benefits of the FC, such as its impact on improving academic performance [24][25][26][27][28][29], the increase in the number of interactions between the participating agents [30][31][32][33] or the motivation inherent in the implementation of this proposal [34][35][36].…”
Section: The Implementation Of the Flipped Classroom In The Universit...mentioning
confidence: 99%
“…Pada dasarnya, konsep model pembelajaran Flipped Classroom yaitu mahasiswa di rumah mengerjakan apa yang dilakukan di kelas yaitu belajar dengan memahami materi yang telah diberikan oleh dosen, dan di kelas mahasiswa mengerjakan apa yang biasanya dikerjakan siswa di rumah yaitu mngerjakan soal dan menyelesaikan masalah. Xiao et al, (2021); Zhang & Feng (2019); Maolidah et al, (2017). Flipped Classroom merupakan suatu cara dalam proses pembelajaran yang mengurangi kapasitas kegiatan pembelajaran di dalam kelas dengan memaksimalkan interaksi satu sama lain yaitu guru, siswa dan lingkungannya.…”
Section: Pendahuluanunclassified